Faktor-faktor pendukung membuka usaha bagi pekerja pariwisata yang dirumahkan di kota denpasar - Pratiwi, A.A Manik; Kesumadewi, Putu Diah (Jurnal Kepariwisataan dan Hospitalitas, 2022)
Abstract     As a result of Covid-19, many countries have closed international airports, this of course has a huge impact on the tourism sector in Bali. Since April 2020, nearly 96 percent of hotels in Bali have closed and laid off their workers. The status of these workers was laid off (taking unpaid leave). Tourism workers who lost their jobs did not just give up, they do everything to make money. Many of the laid-off tourism workers have switched professions to become new seller who use their cars and selling on the side of the main road in Denpasar City. This study aims 1) to find supporting factors in opening a business for laid-off tourism workers during the Covid – 19 pandemic, 2) to find out the most dominant factor which is a supporting factor in opening a business for laid-off tourism workers during the Covid-19 pandemic. Research location in Denpasar City. This study used 100 respondents with accidental sampling technique. The data will be analyzed using quantitative descriptive analysis and factor analysis. Based on the results of calculations using factor analysis, there are 12 variables grouped into 3 factors, namely business relations and business management factors, internal and external factors, and self-motivation factors which are supporting factors in opening a business for laid-off tourism workers during the Covid-19 pandemic. Of the three factors, business relations and business management are the most dominant. Conclusions from this research need to be hold entrepreneurship training activities for laid-off tourism workers so that they have entrepreneurial skills that are very useful for develop their business.   Keywords : supporting, factors, business, laid-off, tourism, workers.